Dynamic Interconversions of Single Molecules Probed by Recognition Tunneling at Cucurbit[7]uril‐Functionalized Supramolecular Junctions. Issue 26 (5th May 2022) - Xiao, Bohuai; He, Suhang; Sun, Mingjun; Zhou, Jianghao; Wang, Zhiye; Li, Yunchuan; Liu, Simin; Nau, Werner M.; Chang, Shuai
Abstract: We introduce a versatile recognition tunneling technique using doubly cucurbit[7]uril‐functionalized electrodes to form supramolecular junctions that capture analytes dynamically by host–guest complexation. This results in characteristic changes in their single‐molecule conductance. For structurally related drug molecules (camptothecin, sanguinarine, chelerythrine, and berberine) and mixtures thereof, we observed distinct current switching signals related to their intrinsic conductance properties as well as pH‐dependent effects which can be traced back to their different states (protonated versus neutral). The conductance variation of a single molecule with pH shows a sigmoidal distribution, allowing us to extract a p K a value for reversible protonation, which is consistent with the reported macroscopic results. The new electronic method allows the characterization of unmodified drug molecules and showcases the transfer of dynamic supramolecular chemistry principles to single molecules. Abstract : Dynamic conversions of single molecules can be monitored at doubly cucurbit[7]uril‐functionalized supramolecular junctions. Through this intermolecular recognition tunneling technique, the molecular conductance of different analytes and analyte mixtures can be finger‐printed in dependence on pH and competitive salts, showcasing the first examples of direct as well as displacement titrations of single host–guest complexes at electronic junctions.